ANALISIS PENGARUH TEKNOLOGI INFORMASI TERHADAP MOTIVASI BELAJAR SISWA SMK YASPIKA DI TANJUNG BALAI KARIMUN - Jurnal Ilmiah Manajemen Universitas Putera Batam (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
Technology development had been advanced and increasing rapidly, where today almost all the learning activities carried out on the basis of the system. One example is SMK YASPIKA Tanjung Balai Karimun. This study aims to determine whether the information technology affects the student’s motivation or not. The object of research is taken from students at SMK YASPIKA in Tanjung Balai Karimun. Use saturated sampling technique for collecting samples and its involved 239 respondents. The analytical method used is simplified linear regression set of information technology as an independent variable and student motivation as the dependent variable. Results of analysis in this study using SPSS version 20 indicates that information technology (X) has an effect on student motivation (Y) using T test, and test results indicate that the effect of R student motivation is not only influenced by information technology variable but also other variables which are not examined in this study.